(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
تمّ دراسة تأثير عامل الحرارة (100 و 121 °م) والزمن (1،2،3،4،5 سا) في أثناء استخلاص الاغار من الطحلب الأحمر Pterocladia capillacea على مردود وبعض الخصائص الفيزيائية والكيميائية للاغار المنتج. بلغ أعلى مردود من الاغار 36% عندما كانت الحرارة 100°م و الزمن 4 سا ويتميز الاغار المنتج بدرجة تجمد 31 °م و درجة ذوبان 84°م وقوة تهلم 431 غ/سم2. أما قيمة مردود الاغار بعد المعالجة القلوية فكانت 18 %بدرجة حرارة 100 و زمن 2سا، بينما كانت قوة التهلم 1072 غ/سم2 وهي أعلى من الاغار الطبيعي. اعتماداً على هذه النتائج، يمكن أن يشكل الطحلب Pterocladia capillacea مصدراً هاما لإنتاج الاغار التجاري مستقبلا. The effects of temperatures (100 C° and 121C°) and extraction time (1, 2, 3, 4,5h) of agar from the Pterocladia capillacea have been studied on the yield and some physicochemical properties of extracted agar.The maximum agar yield (36%) has been obtained with time 4h and temperature 100C° which is characterized by a gelling temperature of 31C° and a melting temperature of 84C° with gel strength 431 g/cm². After alkali treatment, the yield (18%) obtained with time 2h and temperature 100C° was lower in comparison to non-alkali treated agar, while gel strength agar (1072 g/cm²) was significantly higher of gel strength agar native. Based on the results of this study, this alga is a potentially good source for the production of commercial agar in the future.